Dengeki Daisy. Vol. 4 - Motomi, Kyousuke (Shojo beat manga., 2011)
"Discovering DAISY's true identity not only shocks Teru but makes things more confusing for her as well. Meanwhile, someone pretending to be DAISY threatens to spread a computer virus at school! But who's the true target of this attack?"--Publisher's web site.